Electrolyte membrane, membrane electrode assembly, electrochemical cell, and method for manufacturing electrolyte membrane
By incorporating multiple crystal domains with varying concentrations of substitution elements, the electrolytic film enhances proton conductivity, addressing the limitations of existing films and improving performance in electrochemical applications.
Patent Information
- Application Number
- JP2021569780
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-07
- Filing Date
- 2020-12-09
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-12-09
AI Technical Summary
Existing electrolytic films exhibit low proton conductivity at elevated temperatures, limiting their performance in electrochemical applications.
The electrolytic film is composed of multiple crystal domains, with each domain having a distinct concentration of a triple substitution element, such as Yb, resulting in a heterogeneous distribution that enhances proton conductivity.
The film achieves higher proton conductivity at temperatures between 500 to 700 degrees Celsius, outperforming films with uniform element concentrations by up to 0.03 S·cm⁻¹, demonstrating improved performance in electrochemical cells and fuel cells.
Smart Images

Figure 0007624633000004 
Figure 0007624633000005 
Figure 0007624633000006
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrolyte membrane, a membrane electrode assembly, and a method for manufacturing an electrolyte membrane for an electrochemical cell.
Background Art
[0002] As an electrolyte material having proton conductivity, a perovskite-type ion conductor having the chemical formula BaZr 1-x M x O 3-α (where M is a trivalent substitution element) is known.
[0003] In Patent Document 1, BaZr 1-x M x O 3-α (where M is at least one element selected from Sc, In, Lu, and Yb, and 0 < x < 1) is disclosed.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] An object of the present disclosure is to provide an electrolyte membrane having a high proton conductivity.
Means for Solving the Problems
[0006] The electrolyte membrane according to the present disclosure is an electrolyte membrane including a plurality of crystal domains, wherein at least one crystal domain includes a first sub-crystal domain and a second sub-crystal domain inside thereof, and the first sub-crystal domain and the second sub- crystal crystal domain each include Ba, Zr, M, and O, M is a trivalent element, and the concentration of M in the first sub-crystal domain is different from the concentration of M in the second sub-crystal domain.
[0007] The method for manufacturing an electrolyte membrane according to the present disclosure includes mixing a material containing BaZr 1-d M d O 3-δ’ with a material containing BaM2O4, where M is a trivalent element and 0 < d < 1 and 0 < δ’ < 1 are satisfied.
Advantages of the Invention
[0008] The present disclosure provides an electrolyte membrane having high proton conductivity.
Brief Description of the Drawings
[0009] [Figure 1] FIG. 1 schematically shows a cross-sectional STEM of an electrolyte membrane according to an embodiment. [Figure 2A] FIG. 2A is a cross-sectional view of a membrane electrode assembly according to an embodiment. [Figure 2B] FIG. 2B is a cross-sectional view of an electrochemical cell according to an embodiment. [Diagram 3] FIG. 3 shows a fuel cell system according to an embodiment. [Figure 4] FIG. 4 shows procedures for fabricating electrolyte membranes, membrane electrode assemblies, and electrochemical cells according to examples and comparative examples. [Diagram 5] FIG. 5 is a cross-sectional STEM image of an electrolyte membrane according to Example 1. [Figure 6A] FIG. 6A is FE-EPMA data (unit: number of counts) of the Yb element of the membrane electrode assembly according to Example 1. [Figure 6B] FIG. 6B is FE-EPMA data (unit: wt%) of the Yb element of the membrane electrode assembly according to Example 1. [Figure 7] FIG. 7 shows the ratio of Yb at each analysis point of the membrane electrode assembly according to Example 1. [Figure 8] FIG. 8 shows a Cole-Cole plot of the cell according to Example 1. [Figure 9] FIG. 9 is a cross-sectional STEM image of an electrolyte membrane according to Example 2. [Figure 10A] FIG. 10A shows FE-EPMA data (unit: count number) of the Yb element of the membrane electrode assembly according to Example 2. [Figure 10B] FIG. 10B is FE-EPMA data (unit: weight %) of the Yb element of the membrane electrode assembly according to Example 2. [Figure 11] FIG. 11 shows the proportion of Yb at each analysis point of the membrane electrode assembly according to Example 2. [Figure 12] FIG. 12 is a cross-sectional STEM image of the electrolyte membrane according to Comparative Example 1. [Figure 13A] FIG. 13A shows FE-EPMA data (unit: count number) of the Yb element of the membrane electrode assembly according to Comparative Example 1. [Figure 13B] FIG. 13B shows FE-EPMA data (unit: weight %) of the Yb element of the membrane electrode assembly according to Comparative Example 1. [Figure 14] FIG. 14 shows the proportion of Yb at each analysis point of the membrane electrode assembly according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Definition of terms) As used herein, the term "STEM" means scanning transmission electron microscope.
[0011] As used herein, the term "FE-EPMA" means an electron probe microanalyzer.
[0012] As used herein, the term "EDX" means energy dispersive X-ray.
[0013] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings.
[0014] (Embodiment 1) FIG. 1 is a schematic diagram showing a cross-sectional STEM image of an electrolyte membrane 11 according to the first embodiment.
[0015] As shown in FIGS. 5 and 9, which are cross-sectional STEM images of the electrolyte membrane 11 obtained in Examples 1 and 2 described below, the electrolyte membrane 11 is composed of a plurality of crystal domains 100.
[0016] The plurality of crystalline domains 100 includes a first crystalline domain 100a and a second crystalline domain 100b.
[0017] 1, each crystalline domain 100 is composed of a first sub-crystalline domain 101 and a second sub-crystalline domain 102. In other words, at least one crystalline domain 100 includes a first sub-crystalline domain 101 and a second sub-crystalline domain 102 therein.
[0018] A grain boundary gb is formed between two adjacent crystal domains 100 (for example, between a first crystal domain 100a and a second crystal domain 100b). The grain boundary gb defines the boundary between the two adjacent crystal domains. Each crystal domain 100 is surrounded by multiple grain boundaries gb in the STEM image. In other words, each crystal domain 100 is defined by multiple grain boundaries gb in the STEM image.
[0019] The first sub-crystalline domain 101 and the second sub-crystalline domain crystal Each of the domains 102 contains Ba, Zr, M, and O, where M is a trivalent element. M may be at least one element selected from Sc, In, Lu, and Yb. The concentration of M in the first sub-crystalline domain 101 is different from the concentration of M in the second sub-crystalline domain 102. In the first embodiment, for example, the concentration of M in the first sub-crystalline domain is higher than the concentration of M in the second sub-crystalline domain, and further, within each crystalline domain 100, the first sub-crystalline domain 101 is surrounded by the second sub-crystalline domain 102.
[0020] In embodiment 1, M is, for example, Yb, and the first and second sub-crystalline domains are, respectively, BaZr 1-a Yb a O 3-δand BaZr 1-b Yb b O 3-δ It is composed of an oxide represented by (where 0 < a < 1, 0 < b < 1, 0 < δ < 1, and (a - b) ≥ 0.28).
[0021] As demonstrated in Examples 1 and 2 described later, when the concentration of M in the first sub-crystalline domain 101 is different from the concentration of M in the second sub-crystalline domain 102, the electrolyte membrane 11 according to Embodiment 1 has a high proton conductivity at a temperature of 500 °C or higher and 700 °C or lower. In Examples 1 and 2, an example using Yb as M is shown, but even when other elements are used, if the concentration of M in the first sub-crystalline domain 101 is different from the concentration of M in the second sub-crystalline domain 102, it has a high proton conductivity at a temperature of 500 °C or higher and 700 °C or lower.
[0022] When there is no sub-crystalline domain, that is, when the concentration of M in the first sub-crystalline domain 101 is substantially the same as the concentration of M in the second sub-crystalline domain 102, as demonstrated in Comparative Example 1 described later, the proton conductivity at a temperature of 500 °C or higher and 700 °C or lower is 0.22 (10 -2 S·cm -1 ) or less. Thus, when there is no sub-crystalline domain, the proton conductivity is low when compared under the same temperature conditions.
[0023] Here, "the concentration of M in the first sub-crystalline domain is substantially the same as the concentration of M in the second sub-crystalline domain" means that (i) When (a - b) ≤ 0.156 in BaZr 1-a M a O 3-δ contained in the first sub-crystalline domain and BaZr 1-b M b O 3-δ contained in the second sub-crystalline domain, (ii) When the value of "maximum weight percent of M - average weight percent of M" per unit area in the data output from an analysis of a 3 × 3 μm area of the electrolyte membrane using an electron beam microanalyzer as described below is 2.0% or less, (iii) When the proportion of M determined by FE-EPMA analysis as described below falls within the range of the average composition value + 0.1 (i.e., c + 0.1 ≧ x), This means that either
[0024] In this case, "the concentration of M in the first sub-crystalline domain is different from the concentration of M in the second sub-crystalline domain" means (i) BaZr in the first sub-crystalline domain 1-a M a O 3-δ and BaZr in the second subcrystalline domain 1-b M b O 3-δ If (ab)>0.156 in (ii) When the value of "maximum weight percent of Yb - average weight percent of Yb" per unit area of the data output from an electron beam microanalyzer analyzing an area of 3 × 3 μm of the electrolyte membrane exceeds 2.0%, (iii) When the Yb ratio obtained from the FE-EPMA analysis is not within the range of the average composition value + 0.1 (i.e., c + 0.1 <x) means...
[0025] As demonstrated in Examples 1 and 2 described later, when the value of (ab) is 0.28 or more, the electrolyte membrane 11 according to embodiment 1 has high proton conductivity at temperatures of 500 degrees Celsius or more and 700 degrees Celsius or less.
[0026] When the value of (ab) is smaller than 0.28, for example, when (ab)≦0.156, the proton conductivity at a temperature of 500° C. or higher and 700° C. or lower is 0.22 (10 -2 S cm -1) or less. If the value of (ab) is smaller than 0.28, the proton conductivity is low when compared under the same temperature conditions.
[0027] More specifically, at a temperature in the range of 500° C. to 700° C., an electrolyte membrane having an (ab) value of 0.28 or more (i.e., the electrolyte membrane according to embodiment 1) has a higher proton conductivity than an electrolyte membrane having an (ab) value of less than 0.28. As an example, an electrolyte membrane having an (ab) value of 0.28 or more (i.e., the electrolyte membrane according to embodiment 1) at a temperature of 600° C. has a proton conductivity of 0.24 (10 -2 S cm -1 ) or more, while having a value of (ab) less than 0.28, the electrolyte membrane has a proton conductivity of 0.21 (10 -2 S cm -1 ) proton conductivity.
[0028] Preferably, the formula (ab) ≧ 0.30 is satisfied. More preferably, the formula (ab) ≧ 0.35 is satisfied. The value of a is the amount of Zr vacancy (in other words, the amount of Yb dopant). The value of δ is the amount of oxygen vacancy. The value of δ satisfies 0<δ<1.
[0029] When a cross section of the electrolyte membrane 11 according to the first embodiment is analyzed by FE-EPMA, it becomes clear that the electrolyte membrane 11 contains a barium zirconate-based compound doped with ytterbium, as demonstrated in Examples 1 and 2 described below. The value of "maximum weight percent of Yb - average weight percent of Yb" per unit area of the data output by the analysis by FE-EPMA (hereinafter, sometimes referred to as "difference in Yb") is 5% or more. At a certain temperature between 500 degrees Celsius and 700 degrees Celsius, an electrolyte membrane with a difference in Yb of 5% or more has a higher proton conductivity than an electrolyte membrane with a difference in Yb of less than 5%. As an example, at a temperature of 600 degrees Celsius, the proton conductivity of the electrolyte membrane 11 is 0.24 (10 -2 S cm -1) has the above high proton conductivity. When the difference in Yb is less than 5%, for example, 2.0% or less, at a temperature of 600 degrees Celsius, as demonstrated in Comparative Example 1, it has a low proton conductivity of 0.21 (10 -2 S·cm -1 ).
[0030] More desirably, the difference in Yb is 6% or more. At a certain temperature between 500 degrees Celsius and 700 degrees Celsius, an electrolyte membrane with a Yb difference of 6% or more has a high proton conductivity of 0.24 (10 -2 S·cm -1 ) or more. In case the difference in Yb is less than 6%, as demonstrated in Example 2 and Comparative Example 1, at a temperature of 500 degrees Celsius, it has a low proton conductivity of 0.19 (10 -2 S·cm -1 ) or less.
[0031] Analyzing the cross-section of the electrolyte membrane 11 according to Embodiment 1, as demonstrated in Example 1 and Example 2, it becomes clear that a 3×3 μm square region represented by the composition formula BaZr 1-x Yb x O 3-δ (where 0 < c < 1, (c + 0.1) < x, 0 < δ < 1) exists on the electrolyte membrane. Here, the value of x is the amount of Zr deficiency (in other words, the amount of Yb dopant). Also, x < 1 may be satisfied. Here, the value of c indicates the ratio of Yb to the sum of Zr and Yb. This ratio is calculated from the charged amounts of the starting materials. The value of c satisfies the formula: 0 < c < 1. The value of c may satisfy the formula: 0 < c < 0.4. The electrolyte membrane 11 according to this embodiment has a high proton conductivity of 0.24 (10 -2 S·cm -1 ) or more at a temperature of 600 degrees Celsius. In case the region where the mathematical formula (c + 0.1) < x does not exist in the electrolyte membrane, at a temperature of 600 degrees Celsius, as demonstrated in Comparative Example 1, it has a low proton conductivity of 0.21 (10 -2 S·cm -1 ).
[0032] The electrolyte materials are synthesized by the citrate complex method, the solid-phase sintering method, the co-precipitation method, the nitrate method, and the spray granulation method.
[0033] (Embodiment 2) 2A shows a cross section of a membrane electrode assembly 10 according to embodiment 2. The membrane electrode assembly 10 includes an electrolyte membrane 11 and an electrode 12. In other words, the electrode 12 is provided on one main surface of the electrolyte membrane 11.
[0034] The electrolyte membrane 11 is as described in embodiment 1. The thickness of the electrolyte membrane 11 is, for example, 1 to 50 μm.
[0035] The electrode 12 primarily comprises at least one of the following compounds: (i) A mixture of an electrolyte material contained in an electrolyte membrane, one or more metals selected from the group consisting of Co, Fe, Pt, and Pt, and Ni (i.e., a cermet). (ii) Lanthanum-containing composite oxides (iii) Barium-containing composite oxides (iv) Strontium-containing composite oxides
[0036] The electrode 12 has a thickness of, for example, 1 to 1000 μm. When the electrode 12 also serves as a support for the cell, the electrode 12 desirably has a thickness of 100 μm to 500 μm. When a component other than the electrode 12 serves as a support for the cell, the electrode 12 desirably has a thickness of 10 μm to 20 μm.
[0037] In FIG. 2A, the electrolyte membrane 11 and the electrode 12 are in contact with each other. However, another layer may be provided between the electrolyte membrane 11 and the electrode 12. An example of the another layer is a functional layer. The functional layer is a layer that promotes the transfer of electrons or protons between the electrolyte membrane 11 and the electrode 12. The functional layer is made of, for example, a composite of a cermet and a complex oxide.
[0038] The electrolyte membrane is fabricated by tape casting, spin coating, dip coating, sputtering, or PLD (Pulse Laser Deposition). The electrolyte membrane is produced by mixing a material containing BaZr 1-d M d O 3-δ’ and a material containing BaM2O4, and then, for example, preparing an electrolyte ceramic slurry containing the mixed material and manufacturing it using the doctor blade method. Here, 0 < d < 1 and 0 < δ’ < 1 are satisfied, M is a trivalent element, and may be at least one element selected from Sc, In, Lu, and Yb. By manufacturing in this way, an electrolyte material in which the concentration of M in the first sub-crystalline domain is different from the concentration of M in the second sub-crystalline domain can be fabricated. The production of the electrolyte membrane may include, for example, adding a powder of BaM2O4 to a powder of BaZr 1-d M d O 3-δ .
[0039] (Embodiment 3) FIG. 2B shows a cross-section of an electrochemical cell 20 including a membrane electrode assembly 10.
[0040] The electrochemical cell 20 includes an electrode 12, an electrolyte membrane 11, and a counter electrode 13.
[0041] The membrane electrode assembly 10 has been described in Embodiment 2.
[0042] As shown in FIG. 2B, in the electrochemical cell 20, the electrode 12, the electrolyte membrane 11, and the counter electrode 13 are laminated in this order. That is, the electrolyte membrane 11 is sandwiched between the electrode 12 and the counter electrode 13. In other words, the electrolyte membrane 11 is provided between the electrode 12 and the counter electrode 13.
[0043] When the counter electrode 13 functions as an air electrode, the counter electrode 13 contains a composite compound. For example, the counter electrode 13 mainly contains lanthanum strontium cobalt oxide. The counter electrode 13 can be provided on the membrane electrode assembly 10 by the screen printing method.
[0044] 2B, the counter electrode 13 and the electrolyte membrane 11 are provided in contact with each other, but the present invention is not limited to this. Another layer may be provided between the counter electrode 13 and the electrolyte membrane 11.
[0045] The other layer can be, for example, a functional layer, which is described in the second embodiment.
[0046] The electrochemical cell 20 may be used in fuel cells, electrochemical hydrogen pumps, hydrogen sensors and water electrolysis devices.
[0047] (Embodiment 4) FIG. 3 shows a schematic of a fuel cell system 1000 including an electrochemical cell.
[0048] The electrochemical cell 20 is described in embodiment 3.
[0049] The electrochemical cells 20 are stacked to obtain a stack 30. The obtained stack 30 is stored in a housing 1014.
[0050] The housing 1014 may be made of a heat insulating material. An oxidant gas is supplied to the counter electrodes 13 of the stacked electrochemical cells 20.
[0051] Specifically, the oxidant gas is supplied from an oxidant gas supplier 1021 through an oxidant gas passage 1024 to the counter electrodes 13 (ie, cathodes) of the multiple electrochemical cells 20 .
[0052] At the counter electrode 13, the following reaction (1) proceeds. O2+4H + +4e - →2H2O (1)
[0053] The oxidant gas is, for example, air.
[0054] The raw material is supplied from a raw material supplier 1022 through a raw material gas path 1023 to the electrode 12 .
[0055] At the electrode 12, the following reaction (2) proceeds: 2H2→4H + +4e - (2)
[0056] The raw material is, for example, hydrogen molecules.
[0057] The hydrogen may be produced by a reforming reaction. Alternatively, the hydrogen may be produced by water electrolysis.
[0058] In this manner, the fuel cell system 1000 operates and generates power.
[0059] (Example) (Production and Characterization of Cells in Examples and Comparative Examples) The present disclosure will now be described in more detail with reference to the following examples and comparative examples. As described below, in Example 1, Example 2, and Comparative Example 1, electrolyte membranes and membrane electrode assemblies / cells using the same were produced. Then, the characteristics of each electrolyte membrane and each membrane electrode assembly / cell were evaluated.
[0060] Example 1 (Production of electrolyte membranes and membrane electrode assemblies / cells using the same) With reference to FIG. 4, the preparation of an electrolyte membrane and a membrane electrode assembly / cell using the same will be described.
[0061] (1) Preparation of electrolyte green sheet (1A) Preparation of Electrolyte Ceramic Slurry (see S100) First, the preparation of the ceramic slurry used to obtain the electrolyte green sheets will be described.
[0062] The following materials were prepared as starting materials for the electrolyte material:
[0063] Ba(NO3)2 (Kanto Chemical Co., Ltd.) 0.100 mol ZrO(NO3)2·2H2O (manufactured by Kanto Chemical Co., Inc.) 0.085 mol Yb(NO3)3·xH2O (2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.015 mol
[0064] The above starting materials were added to distilled water to obtain a mixed solution, and then the mixture was stirred.
[0065] Then, citric acid monohydrate (0.1 mol, manufactured by Kanto Chemical Co., Inc.) and ethylenediaminetetraacetic acid (0.2 mol, manufactured by Kanto Chemical Co., Inc., hereinafter referred to as "ethylenediaminetetraacetic acid" as EDTA) were added to the mixed solution. Thereafter, the mixed solution was stirred at a temperature of 90°C.
[0066] Then, aqueous ammonia (28% by weight, manufactured by Kanto Chemical Co., Inc.) was added to the mixed solution. Next, at a temperature of 90°C, using a pH meter (manufactured by Horiba, Ltd.), the pH of the mixed solution was adjusted to 7.
[0067] After adjusting the pH of the mixed solution to 7, using a hot stirrer, the temperature of the mixed solution was raised from 95°C to 240°C to evaporate the solvent (i.e., water). In this way, water was removed from the mixed solution to obtain a solid.
[0068] After the obtained solid was pulverized in a mortar, it was degreased at a temperature of about 400°C. In this way, a powder was obtained.
[0069] Using a hydraulic pump (manufactured by Enapac Co., Ltd.) and a powder molding die having a diameter of 30 millimeters, the obtained powder was pressed into a cylindrical shape. In this way, a cylindrical molded product was obtained.
[0070] Thereafter, the obtained circular molded product was calcined at 900°C for 10 hours in an air atmosphere. In this way, a calcined powder was obtained.
[0071] Then, the calcined powder was pulverized. Next, the pulverized powder was transferred to a plastic container together with zirconia balls.
[0072] Then, ethanol (100 g, manufactured by Kanto Chemical Co., Ltd.) was added to the plastic container. Thus, a mixed liquid was obtained. Next, the mixed liquid was pulverized in a ball mill for 4 days.
[0073] After the grinding with the ball mill, the mixture was dried with a lamp to remove the ethanol from the mixture, thus obtaining a powder.
[0074] The obtained powder was sintered at 1200°C for 5 hours in air. 1-d M d O 3-δ’ A material equivalent to (M is Yb) was created. Furthermore, BaYb2O4 powder (3 mol% based on the sintered powder) was added to the sintered powder to obtain Ba 0.97 Zr 0.80 Yb 0.20 O 3-δ (δ is the amount of oxygen vacancy, 0<δ<1.0) electrolyte material was prepared.
[0075] Next, the following materials were mixed to prepare an electrolyte ceramic slurry (see S100):
[0076] Ba 0.97 Zr 0.80 Yb 0.20 O 3-δ 50g electrolyte material Polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd.) 5g Butyl benzyl phthalate (Kanto Chemical Co., Ltd.) 1.25g Mixed solvent 40g
[0077] The mixed solvent was composed of butyl acetate (20 g, manufactured by Kanto Chemical Co., Ltd.) and 1-butanol (20 g, manufactured by Kanto Chemical Co., Ltd.) In this manner, an electrolyte ceramic slurry was prepared.
[0078] (1B) Preparation of electrolyte green sheets (see S101 and S102) Next, a film made of an electrolyte ceramic slurry was formed on a support sheet made of a polyethylene terephthalate film having a thickness of about 50 μm by the doctor blade method (see S101). The obtained film made of the slurry was heated at a temperature of 80 °C to evaporate the solvent. In this way, an electrolyte green sheet was produced (see S102). The electrolyte green sheet had a thickness of about 21 μm.
[0079] (2) Preparation of electrode green sheet Next, an electrode green sheet was produced in the same manner as the method for producing the electrolyte green sheet, except for the matters described in detail below.
[0080] (2A) Preparation of electrode ceramic slurry (see S200) Except that the following materials were prepared as starting materials for the electrodes instead of the starting materials for the electrolyte materials, Ba 1.00 Zr 0.85 Yb 0.15 O 3-δ (where δ is the amount of oxygen deficiency, 0 < δ < 1.0), an electrolyte material was prepared in the same manner as the method for preparing the electrolyte material.
[0081] Ba(NO3)2 (manufactured by Kanto Chemical Co., Inc.) 0.097 mol ZrO(NO3)2·2H2O (manufactured by Kanto Chemical Co., Inc.) 0.08 mol Yb(NO3)3·xH2O (2 < x < 6, manufactured by High Purity Chemical Research Institute Co., Ltd.) 0.02 mol
[0082] In this way, Ba 1.00 Zr 0.85 Yb 0.15 O 3-δ (where δ is the amount of oxygen deficiency, 0 < δ < 1.0) was replaced with Ba 0.97 Zr 0.8 Yb 0.2 O 3-δ an electrolyte material was obtained.
[0083] The electrode ceramic slurry was prepared by mixing the following materials.
[0084] Ba 0.97 Zr 0.8 Yb 0.2 O 3-δ 20g electrolyte material Polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd.) 5g Butyl benzyl phthalate (Kanto Chemical Co., Ltd.) 1.25g NiO (Sumitomo Metal Mining Co., Ltd.) 30g Mixed solvent 40g
[0085] The mixed solvent consisted of butyl acetate (20 g, Kanto Chemical Co., Ltd.) and 1-butanol (20 g, Kanto Chemical Co., Ltd.).
[0086] (2B) Preparation of electrode green sheets (see S201 and S202) Next, a film made of the electrode ceramic slurry was formed on a support sheet made of a polyethylene terephthalate film having a thickness of about 50 μm by a doctor blade method (see S201). The film made of the slurry had a thickness of about 30 μm. The obtained film made of the slurry was heated at a temperature of 80° C. In this way, an electrode green sheet was produced.
[0087] (3) Lamination of sheets (see S300 to S303) The electrolyte green sheet was cut to obtain one cut electrolyte green sheet. Then, the polyethylene terephthalate film was peeled off from the electrolyte green sheet. The cut electrolyte green sheet had a size of 140 mm x 140 mm. The electrode green sheet was cut to obtain one cut electrode green sheet. The cut electrode green sheet had a size of 140 mm x 140 mm.
[0088] A plurality of cut electrode green sheets were stacked to obtain a laminate having a thickness of about 700 μm.
[0089] Thereafter, the laminate was hot-pressed under conditions of 85° C. and 13 MPa, thus producing an electrode.
[0090] Furthermore, one cut electrolyte green sheet was laminated on one main surface of the electrode to obtain a laminate (see S300), and the obtained laminate was then hot pressed.
[0091] The hot pressing was carried out under conditions of 80° C. and 13 MPa. In this manner, a molded body was obtained.
[0092] The obtained molded body was further pressed at a pressure of 50 MPa (by Sansho Industry Co., Ltd.) to obtain a laminate (see S301). The thickness was almost unchanged, being about 700 μm.
[0093] The laminate was cut to a size of 20 mm x 20 mm (see S302).
[0094] Finally, the cut laminate was sintered in an air atmosphere at 1400° C. for 2 hours. In this manner, a membrane electrode assembly according to Example 1 was produced (see S303, one of the cut laminates is shown in the figure). The membrane electrode assembly was an assembly of an electrolyte membrane and an electrode.
[0095] (4) Formation of the counter electrode (see S304 and S305) Furthermore, a counter electrode was provided on the obtained membrane electrode assembly. The counter electrode was provided in the following manner. The following materials were prepared as starting materials for the counter electrode.
[0096] NiO (Sumitomo Metal Mining Co., Ltd.) 5g Polyethylene glycol 400 (Wako Pure Chemical Industries, Ltd.) 1g Ethanol (Kanto Chemical Co., Ltd.) 40g
[0097] Various starting materials were added to a ball mill and mixed. In this way, a mixture was obtained. The mixture obtained was then heated to 150°C using a hot stirrer. In this way, a NiO paste was obtained.
[0098] Next, NiO paste was applied by screen printing to one of the main surfaces of the membrane electrode assembly where the electrolyte membrane was exposed (see S304). The applied NiO paste had a diameter of 10 mm. In this way, a cell precursor was obtained.
[0099] Then, the cell precursor was sintered in an air atmosphere for 2 hours at 1400° C. In this manner, the cell according to Example 1 was produced (see S305).
[0100] (Cell analysis 1: STEM analysis, EDX analysis) The electrolyte membrane of the cell according to Example 1 was analyzed by STEM. Specifically, the obtained membrane electrode assembly was cut, and the cross section of the membrane electrode assembly was analyzed by STEM. Hereinafter, the analysis by STEM may be referred to as "STEM analysis."
[0101] The STEM used for the analysis was JEM-F200 (manufactured by JEOL Ltd.) The STEM analysis was carried out under an accelerating voltage of 200 kV.
[0102] Figure 5 is a bright-field STEM image of the electrolyte membrane. The circles in Figure 5 indicate the areas analyzed by EDX. Hereinafter, analysis by EDX may be referred to as "EDX analysis."
[0103] The ratios of Zr and Yb elements (i.e., weight ratios) were calculated from the characteristic X-ray intensities obtained by EDX analysis using the well-known Cliff-Lorimer method. Table 1 shows the ratios of Zr and Yb for all the analyzed points.
[0104] (Cell analysis 2: Analysis by FE-EPMA) The electrolyte membrane according to Example 1 was analyzed by FE-EPMA. Hereinafter, the analysis by FE-EPMA may be referred to as "FE-EPMA analysis."
[0105] The FE-EPMA used for the analysis was an EPMA-8050G (manufactured by Shimadzu Corporation). The analysis was performed by FE-EPMA under an accelerating voltage of 15 kV and an irradiation current of 100 nA. An area of 40 × 30 μm including the electrolyte membrane was analyzed.
[0106] Figures 6A and 6B are data output from the FE-EPMA. Figure 6A shows the count number of Yb based on the weight of each element. The count number obtained is an absolute value. The bar on the right side of Figure 6A indicates the relationship between the shading on Figure 6A and the count number.
[0107] FIG. 6B is a graph in which FIG. 6A is converted into relative values (ie, weight %).
[0108] Furthermore, the average, maximum and minimum values of the weight percentage of Yb in a 3×3 μm square region of the electrolyte membrane were outputted using an EPMA-8050G (manufactured by Shimadzu Corporation).
[0109] Table 2 shows data indicating the average, maximum and minimum values of the weight percentage of Yb in a 3×3 μm square region of the electrolyte membrane.
[0110] Based on the data in FIG. 6A, the concentrations of Zr and Yb at each analysis point were determined.
[0111] Based on the data in Figure 6A, the counts were converted to concentrations (i.e., weight %) by the calibration curve method. The number of analysis points was 15,000.
[0112] The value of Yb / (Zr+Yb) (i.e., the composition ratio of Yb) was calculated based on the weight percentages at the 15,000 analysis points. Furthermore, the average value of the 15,000 analysis points was corrected so that Yb / (Zr+Yb)=0.2 (i.e., the average composition of the electrolyte membrane, sometimes indicated as c). This average composition of the electrolyte membrane is calculated from the amounts of the starting materials charged.
[0113] Then, the value of Yb / (Zr+Yb) at each analysis point and the proportion of the 15,000 analysis points that had a predetermined Yb / (Zr+Yb) value were determined.
[0114] FIG. 7 is a graph showing the value of Yb / (Zr+Yb) at each analysis point and the proportion of the 15,000 analysis points that have a given Yb / (Zr+Yb).
[0115] The "Yb ratio" shown in Fig. 7 is the value of Yb / (Zr+Yb). The "frequency (%)" shown in Fig. 7 is the ratio of a given Yb / (Zr+Yb) value in the electrolyte membrane.
[0116] (Cell Analysis 3: Proton Conductivity of Electrolyte Membrane) The proton conductivity of the electrolyte membrane was calculated from the resistance and thickness of the electrolyte membrane using the cell according to Example 1. The resistance of the electrolyte membrane was measured based on an AC impedance method. The method for determining the proton conductivity of the electrolyte membrane is as follows.
[0117] Using ModuLab XM ECS (manufactured by Solartron Analytical), an alternating current was applied to the cell (conditions: humidified hydrogen atmosphere, temperature of 600°C) with an amplitude of 10 mV and a frequency range of 1 MHz to 0.01 Hz. Then, a Cole-Cole plot (see FIG. 8) was output. Based on the arc (see FIG. 8) in the frequency range of 100 kHz to 0.01 Hz of the output Cole-Cole plot, the intersection point between the arc and the real axis was obtained. The real axis is the axis where the Y-axis value in the graph of FIG. 8 is 0. Then, of the intersection points obtained, the intersection point on the high frequency side was taken as the IR resistance (see FIG. 8).
[0118] Based on the required IR resistance and the thickness of the electrolyte membrane, the proton conductivity (unit: 10 -2 S·cm -1 ) of the electrolyte membrane of the cell was calculated.
[0119] Note that the resistance of the electrolyte membrane was also measured at each temperature of 500 °C and 700 °C.
[0120] Table 3 shows the proton conductivity (unit: 10 -2 S·cm -1 ) at each temperature and for the electrolyte membrane.
[0121] (Example 2) In Example 2, an electrolyte membrane of Example 2 and a membrane electrode assembly / cell using the same were fabricated in the same manner as in Example 1, except for the following steps. Then, the electrolyte membrane was analyzed. Next, the characteristics of the membrane electrode assembly / cell were evaluated. Figures 9 and Table 1 show the results of STEM analysis / EDX analysis. Figures 10A, 10B and Table 2 show the results of FE-EPMA analysis. Table 3 shows the result of calculating the proton conductivity of the cell.
[0122] (1) As starting materials for the electrolyte material, the following materials were prepared. Ba(NO3)2 (manufactured by Kanto Chemical Co., Inc.) 0.098 mol ZrO(NO3)2·2H2O (manufactured by Kanto Chemical Co., Inc.) 0.081 mol Yb(NO3)3·xH2O (3 < x < 6, manufactured by High Purity Chemical Research Institute Co., Ltd.) 0.019 mol
[0123] (2) In the step of preparing the electrolyte ceramic slurry, the amount of BaYb2O4 powder added to the sintered powder was set to 1 mol%.
[0124] (Comparative Example 1) In Comparative Example 1, an electrolyte membrane of Comparative Example 1 and a membrane electrode assembly / cell using the same were prepared in the same manner as in Example 1, except for the following steps. Then, the electrolyte membrane was analyzed. Next, the characteristics of the membrane electrode assembly / cell were evaluated. Note that FIGS. 12 and Table 1 show the results of STEM analysis / EDX analysis. FIGS. 13A, 13B and Table 2 show the results of FE-EPMA analysis. Further, Table 3 shows the results of calculating the proton conductivity of the cell.
[0125] (1) As starting materials for the electrolyte material, the following materials were prepared. Ba(NO3)2 (manufactured by Kanto Chemical Co., Inc.) 0.097 mol ZrO(NO3)2·2H2O (manufactured by Kanto Chemical Co., Inc.) 0.080 mol Yb(NO3)3·xH2O (3 < x < 6, manufactured by High Purity Chemical Research Institute Co., Ltd.) 0.020 mol
[0126] (2) In the step of preparing the electrolyte ceramic slurry, the powder of BaYb2O4 was not added to the sintered powder.
[0127] (Results of characteristic evaluation) (Analysis of cell 1: STEM analysis / EDX analysis) Based on FIGS. 5, 9, 12 and Table 1, the results of STEM analysis and EDX analysis will be described. As shown in FIGS. 5 and 9, the electrolyte membranes according to Example 1 and Example 2 are crystalline. The crystalline electrolyte membrane is composed of a plurality of crystal domains. Each crystal domain is composed of a first sub-crystal domain and a second sub-crystal domain. The first sub-crystal domain is surrounded by the second sub-crystal domain. In other words, the first sub-crystal domain is located near the center of each crystal domain. On the other hand, the second sub-crystal domain is located near the periphery of each crystal domain.
[0128] As shown in FIG. 5, analysis points 1-1, 1-3, and 1-5 are observed as black by the naked eye. These analysis points are the first sub-crystalline domain. When this first sub-crystalline domain was analyzed by EDX, the concentration of Yb was higher than the concentration of Zr, as shown in Table 1. On the other hand, analysis points 1-2, 1-4, and 1-6 are observed as white by the naked eye, as shown in FIG. 5. These analysis points are the second sub-crystalline domain. When this second sub-crystalline domain was analyzed by EDX, the concentration of Zr was higher than the concentration of Yb, as shown in Table 1.
[0129] As shown in FIG. 9, the analysis points 2-1 and 2-3 are observed as black by the naked eye. These analysis points are the first sub-crystal domain. When this first sub-crystal domain was analyzed by EDX, the concentration of Yb was higher than the concentration of Zr, as shown in Table 1. On the other hand, as shown in FIG. 9, the analysis points 2-2 and 2-4 are observed as white by the naked eye. These points are the second sub-crystal domain. When this second sub-crystal domain was analyzed by EDX, the concentration of Zr was higher than Yb, as shown in Table 1. Both the analysis points 2-5 and 2-6 are observed as white by the naked eye. Therefore, the crystal domains at the analysis points 2-5 and 2-6 do not have sub-crystal domains.
[0130] 12, the crystalline domains constituting the electrolyte membrane of Comparative Example 1 did not have subcrystalline domains. When the electrolyte membrane of Comparative Example 1 was analyzed by EDX, the Zr concentration was higher than the Yb concentration at every analysis point.
[0131] Therefore, the electrolyte membrane of Comparative Example 1 was an electrolyte membrane having a more homogeneous Yb concentration than the electrolyte membranes of Examples 1 and 2.
[0132] In other words, the electrolyte membranes of Examples 1 and 2 had areas where the concentration of Yb was unevenly distributed, as compared with Comparative Example 1.
[0133] From Example 1 and Example 2, in the electrolyte membrane where the concentration of Yb is unevenly distributed, the difference in Yb / (Zr + Yb) measured in each crystal domain is 0.28 or more. Specifically, the difference in Yb / (Zr + Yb) was 0.29 or more.
[0134] Therefore, the electrolyte membranes according to Example 1 and Example 2 included a plurality of crystal domains. And at least one crystal domain included a first sub-crystal domain and a second sub-crystal domain inside thereof. The concentration of M in the first sub-crystal domain was different from the concentration of M in the second sub-crystal domain. The concentration of M in the first sub-crystal domain was higher than the concentration of M in the second sub-crystal domain. The first sub-crystal domain was surrounded by the second sub-crystal domain. The first sub-crystal domain was represented by the chemical formula BaZr 1-a Yb a O 3-δ and the second sub-crystal domain was represented by the chemical formula BaZr 1-b Yb b O 3-δ Here, each chemical formula satisfied 0 < a < 1, 0 < b < 1, 0 < δ < 1, and a - b ≧ 0.28.
[0135] (Analysis of the cell 2: Analysis by FE-EPMA) Based on FIGS. 7, 11, and 14, the results of the FE-EPMA analysis will be described.
[0136] Yb / (Zr + Yb) = 0.2 (that is, the Yb ratio when taking the average composition. In other words, the Yb ratio of the composition formula BaZr 0.8 Yb 0.2 O 3-δ (δ is the amount of oxygen deficiency, 0 < δ < 1)) The Yb ratios that were farthest from the value were Example 1: Yb / (Zr + Yb) = 0.49, Example 2: Yb / (Zr + Yb) = 0.32, and Comparative Example 1: Yb / (Zr + Yb) = 0.30.
[0137] As shown in Comparative Example 1, when a homogeneous electrolyte membrane was prepared with the Yb concentration being compared with those in Example 1 and Example 2, the Yb ratio determined from FE-EPMA analysis fell within the range of the value of the average composition (i.e., 0.2) + 0.1.
[0138] On the other hand, in Example 1 and Example 2, the Yb ratio determined from FE-EPMA analysis did not fall within the value of the average composition + 0.1. In other words, in Example 1 and Example 2, at least a part of the Yb ratio determined from FE-EPMA analysis had a value greater than the value of the average composition + 0.1. Therefore, it was revealed that the electrolyte membranes according to Example 1 and Example 2 had a non-uniform Yb concentration distribution compared with Comparative Example 1 (i.e., the Yb concentration was unevenly distributed in the electrolyte membrane. Also, the Yb concentrations in the first sub-crystalline domain and the second sub-crystalline domain were different).
[0139] Therefore, the electrolyte membranes according to Example 1 and Example 2 contain a ytterbium-doped barium zirconate-based compound. And a 3×3 μm square region represented by the composition formula BaZr 1-x Yb x O 3-δ (0 < c < 1, c + 0.1 < x, 0 < δ < 1) exists on the electrolyte membrane.
[0140] Next, based on Table 2, the results of the FE-EPMA analysis will be explained.
[0141] Data was output by FE-EPMA analysis. Then, the maximum, minimum, average, and "maximum-average" values of the weight percent of Yb in a 3 μm×3 μm region on the electrolyte membrane were obtained. In Example 1 and Example 2, the "maximum-average" value was 5 or more. Specifically, the "maximum-average" value was 6.2 in Example 1 and 5.6 in Example 2. On the other hand, the "maximum-average" value was 2.0 in Comparative Example 1. Therefore, it was revealed that the electrolyte membranes according to Examples 1 and 2 had a larger difference in Yb concentration than the electrolyte membrane according to Comparative Example 1. In other words, the electrolyte membranes according to Examples 1 and 2 contained a barium zirconate-based compound doped with ytterbium. In the electrolyte membrane of Comparative Example 1, the concentration of M in the first sub-crystal domain and the concentration of M in the second sub-crystal domain were substantially the same. Then, the 3×3 μm range of the electrolyte membrane was analyzed by an electron beam microanalyzer, and data was output. The value of "maximum value of Yb by weight % - average value of Yb by weight %" per unit area of the output data was 5% or more.
[0142] (Cell Analysis 3: Cell Proton Conductivity) Based on Table 3, the proton conductivity of the electrolyte membrane is explained.
[0143] The cells according to Examples 1 and 2 had higher proton conductivity at each temperature (i.e., 500° C., 600° C., and 700° C.) than the cell according to Comparative Example 1. It was therefore revealed that the electrolyte membrane in which the Yb concentration is unevenly distributed and the cell using the electrolyte membrane have improved proton conductivity.
[0144] [Table 1]
[0145] [Table 2]
[0146] [Table 3] [Industrial Applicability]
[0147] The electrolyte membrane according to the present disclosure may be suitable for use in electrochemical cells and fuel cells. [Explanation of symbols]
[0148] 10 Membrane electrode assembly 11 Electrolyte membrane 100 Crystal Domains 100a First Crystal Domain 100b Second Crystal Domain 101 First sub-crystalline domain 102 Second sub-crystalline domain gb grain boundary 12 electrodes 13. Opposite 20 Electrochemical Cell 1000 Fuel Cell System 1014 Case 1021 Oxidant gas supply 1022 Raw material feeder 1023 Raw gas route 1024 Oxidant gas route
Claims
1. An electrolyte membrane, comprising a plurality of crystalline domains; Where: at least one crystalline domain includes a first sub-crystalline domain and a second sub-crystalline domain therein; the first sub-crystalline domain is represented by the formula BaZr 1-a Yb a O 3-δ ; and the second sub-crystalline domain is represented by the formula BaZr1-bYbbO3-δ; Where: 0<a<1, 0<b<1, 0<δ<1, and (a-b) ≧ 0.28 is satisfied; electrolyte membrane.
2. The first sub-crystalline domain is surrounded by the second sub-crystalline domain. The electrolyte membrane according to claim 1 .
3. The formula (a-b) ≧ 0.30 is satisfied; The electrolyte membrane according to claim 1 .
4. The formula (a-b) ≧ 0.35 is satisfied; The electrolyte membrane according to claim 3.
5. A membrane electrode assembly, The electrolyte membrane according to any one of claims 1 to 4, and an electrode provided on the electrolyte membrane; Equipped with Membrane electrode assembly.
6. 1. An electrochemical cell comprising: electrode, The electrolyte membrane according to any one of claims 1 to 4, and The opposite, Equipped with Where: The electrolyte membrane is provided between the electrode and the counter electrode. Electrochemical cell.
7. A method for producing the electrolyte membrane according to claim 1, comprising the steps of: The manufacturing method is BaZr 1-d M d O 3-δ’ Materials containing BaM 2 O 4 and mixing the material with where M is Yb, 0<d<1, and 0<δ'<1. A method for manufacturing an electrolyte membrane.
Citation Information
Patent Citations
Membrane electrode junction body and solid oxide fuel cell
JP2017188439A
Membrane electrode assembly of electrochemical device, fuel battery, electrochemical hydrogen pump, and hydrogen sensor
JP2018088384A
Proton conductor, proton-conducting cell structure, water vapor electrolysis cell, and method for producing hydrogen electrode-solid electrolyte layer complex
WO2019107194A1